Cultivation of Rauwolfia serpentina in Kota Forest Division (Rajasthan) - Mathur, C. M.; Singh, S. P. (Indian Forester, 1965)
Results of studies on root and seed production and alkaloidal content of the roots in the case of about 1,2 and 3 year old plants of Rauwolfia serpentina (Linn.) Benth. Ex Kurz being raispd under irrigated conditions at Kota are given. Average weight of air dried roots per plant from 1, 2 and 3 year old plants is 22 g, 49 g and 162 g respectively. The total alkaloidal content of 1, 2 and 3 year old roots was found to be 1.24, 1.31 and 1.50 per cent respectively and is well above the I.P. and B.P.C. standard (not less than 0.8 per cent). The seed production per plant comes to be 2.1, 3.6 and 8.0 g in case of 1, 2 and 3 year old plants respectively. The results of yield of roots and their alkaloidal content from these plantations at Kota compare favourably with those obtained from plantations raised at Forest Research Institute, Dehra Dun. Possibility of extending the plantations of Rauwolfia serpentina in suitable localities in this state is indicated. Considering the increase in the yield of roots with the age of plants, harvesting of roots from 2 to 3 year old plants is suggested.